Edukasi Stimulasi Perkembangan Melalui Pijat Bayi Di Dusun Jati - Era Revika; Yuni Fitriana (Universitas Jenderal Achmad Yani Yogyakarta, 2020)
Quality human resources determine the future of the nation. Stimulation of growth and development of children from an early age (infancy) is one of the efforts to improve the quality of human resources. Stimulation in infancy can optimize child development because it helps adjust the child's ability and age. Massage is a stimulation of the baby's development through tactile techniques. An important period of children's growth and development can determine the quality of future generations. Basic growth will influence and determine future growth and development. Optimal growth requires more intensive care such as touch and continuous stimulation. One of them is massage. Massage is an effort to fulfill the stimulation needs of children both physically, affectionately, and mentally [1]. Early detection of growth and development abnormalities facilitates the management of stimulation. Based on this, it is necessary to have community service activities aimed at educating developmental stimulation through baby massage. Implementation of education in this activity is carried out through demonstrations, discussions, and questions and answers about the stimulation of child development through baby massage. This activity involves (especially) mothers with 1-year-old babies. Results: The participants were very enthusiastic to participate in this activity. It can be seen from their activeness in discussions and demonstrations. In the demonstration process, the mothers pay attention, follow, and practice baby massage directly to their babies. Conclusion: The participants finally understood the importance of massage stimulation in the development of infants and children.